Nonneutralizing HIV-1 gp41 envelope cluster II human monoclonal antibodies show polyreactivity for binding to phospholipids and protein autoantigens - Dennison, S Moses; Anasti, Kara; Scearce, Richard M; Sutherland, Laura; Parks, Robert; Xia, Shi-Mao; Liao, Hua-Xin; Gorny, Miroslaw K; Zolla-Pazner, Susan; Haynes, Barton F; Alam, S Munir (Journal of virology, 2011)
HIV-1 gp41 envelope antibodies, which are frequently induced in HIV-1-infected individuals, are predominantly nonneutralizing. The rare and difficult-to-induce neutralizing antibodies (2F5 and 4E10) that target gp41 membrane-proximal epitopes (MPER) are polyspecific and require lipid binding for HIV-1 neutralization. These results raise the questions of how prevalent polyreactivity is among gp41 antibodies and how the binding properties of gp41-nonneutralizing antibodies differ from those of antibodies that are broadly neutralizing. In this study, we have characterized a panel of human gp41 antibodies with binding specificities within the immunodominant cluster I (gp41 amino acids [aa] 579 to 613) or cluster II (gp41 aa 644 to 667) for reactivity to autoantigens, to the gp140 protein, and with MPER peptide-lipid conjugates. We report that while none of the gp41 cluster I antibodies studied were polyspecific, all three gp41 cluster II antibodies bound either to lipids or autoantigens, thus showing the propensity of cluster II antibodies to manifest polyreactivity. All cluster II gp41 monoclonal antibodies (MAbs), including those that were lipid reactive, failed to bind to gp41 MPER peptide-lipid complexes. Cluster II antibodies bound strongly with nanomolar binding affinity (dissociation constant [K(d)]) to oligomeric gp140 proteins, and thus, they recognize conformational epitopes on gp41 that are distinct from those of neutralizing gp41 antibodies. These results demonstrate that lipid-reactive gp41 cluster II antibodies are nonneutralizing due to their inability to bind to the relevant neutralizing epitopes on gp41.